Action of Hexachlorobenzene on tumor growth and metastasis in different experimental models - Pontillo, Carolina Andrea (2013)
Hexachlorobenzene (HCB) is a widespread organochlorine pesticide, considered a possible human carcinogen. It is a dioxin-like compound and a weak ligand of the aryl hydrocarbon receptor (AhR). We have found that HCB activates c-Src/HER1/STAT5b and HER1/ERK1/2 signaling pathways and cell migration, in an AhR-dependent manner in MDA-MB-231 breast cancer cells. The aim of this study was to investigate in vitro the effect of HCB (0.005, 0.05, 0.5, 5μM) on cell invasion and metalloproteases (MMPs) 2 and 9 activation in MDA-MB-231 cells. Furthermore, we examined in vivo the effect of HCB (0.3, 3, 30mg/kg b.w.) on tumor growth, MMP2 and MMP9 expression, and metastasis using MDA-MB-231 xenografts and two syngeneic mouse breast cancer models (spontaneous metastasis using C4-HI and lung experimental metastasis using LM3). Our results show that HCB (5μM) enhances MMP2 expression, as well as cell invasion, through AhR, c-Src/HER1 pathway and MMPs. Moreover, HCB increases MMP9 expression, secretion and activity through a HER1 and AhR-dependent mechanism, in MDA-MB-231 cells. HCB (0.3 and 3mg/kg b.w.) enhances subcutaneous tumor growth in MDA-MB-231 and C4-HI in vivo models. In vivo, using MDA-MB-231 model, the pesticide (0.3, 3 and 30mg/kg b.w.) activated c-Src, HER1, STAT5b, and ERK1/2 signaling pathways and increased MMP2 and MMP9 protein levels. Furthermore, we observed that HCB stimulated lung metastasis regardless the tumor hormone-receptor status. Our findings suggest that HCB may be a risk factor for human breast cancer progression.